2022
DOI: 10.5812/semj-120140
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Data Mining Algorithms for Breast Cancer Diagnosis

Abstract: Background: Early screening and diagnosis of breast cancer (BC) is critical for improving the quality of care and reducing the mortality rate. Objectives: This study aimed to construct and compare the performance of several machine learning (ML) algorithms in predicting BC. Methods: This descriptive and applied study included 1,052 samples (442 BC and 710 non-BC) with 30 features related to positive and negative BC diagnoses. The data mining (DM) process was implemented using the selected algorithm, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Afrash et al used Minimum Redundancy Maximum Relevance (mRMR) feature selection with the ensemble and non-ensemble ML algorithms to diagnose COVID-19 based on clinical data [ 36 ]. Shanbehzadeh et al leveraged ML algorithms and preprocessing steps for breast cancer as a single-centered study approach [ 37 ]. They concluded that using the ML techniques plays a significant role in prediction strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Afrash et al used Minimum Redundancy Maximum Relevance (mRMR) feature selection with the ensemble and non-ensemble ML algorithms to diagnose COVID-19 based on clinical data [ 36 ]. Shanbehzadeh et al leveraged ML algorithms and preprocessing steps for breast cancer as a single-centered study approach [ 37 ]. They concluded that using the ML techniques plays a significant role in prediction strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a thermal analysis finite element model of the thermal forming process of ship outer plates, Zhang 15 proposed applying a support vector machine (SVM) to predict local deformation under line heating. Shanbehzadeh 16 conducted a study on early BC prevention based on an ML prediction system and the results showed that machine learning has good predictive power. Nopour 17 chose machine learning techniques to conduct research into the prediction of COVID-19, a model that could help doctors achieve early detection and effective intervention and potentially reduce patient deaths.…”
Section: Introductionmentioning
confidence: 99%